EXPLORING TEACHERS’ ABILITY IN DEVELOPING PISA-LIKE READING TASKS - Fadhillah, Ajeng Meidina; Emilia, Emi (English Review: Journal of English Education, 2022)
This study is a part of a joint study, aiming to develop a teacher professional development program on training teachers to teach PISA-like reading. The bigger program focuses on a pedagogical intervention that incorporates PISA reading into English and Indonesian subjects based on Systemic Functional Linguistics Genre-Based Approach (SFL GBA) and has been reported in Emilia et al. (2022). Meanwhile, this study centred around the observation of English teachers’ ability to develop PISA-like reading tasks. The intervention is framed within PISA reading (OECD, 2019a,b), and SFL GBA (Halliday & Matthiesen, 2014; Derewianka & Jones, 2016; Emilia, 2011). The study employed a case study design. The findings show that teachers were able to develop PISA-like reading tasks, evidenced from the collected reading items that follow PISA 2018 cognitive processes and response format (OECD, 2019 a, b). Moreover, teachers’ responses from interviews were likewise positive, indicating their increased awareness of PISA and their ability to design similar reading tasks. It is recommended that the training be conducted in a variety of settings with a larger number of teachers for them to eventually assist Indonesian students in improving their reading literacy as suggested by PISA.